Impact of abnormal placentation on the risk of hypertensive disorders in pregnancy: A retrospective analysis - Gulay Balkas (Medicine Science)
We aimed to investigate the impact of abnormal placental location and placenta accreta spectrum (PAS) disorders on the incidence of hypertensive disorders of pregnancy. This retrospective, single-center study was conducted at a tertiary maternity hospital between 2018 and 2022. The study population was classified according to abnormal placentation, including control (normal placentation), low-lying placenta (LP), placenta previa (PP), and PAS. The PAS group was further divided into subtypes: accreta, increta, percreta. Logistic regression analysis was performed to evaluate factors influencing the incidence of HDPs and pregnancy-induced hypertension (PIH) and their association with abnormal placentation and PAS subtypes. A total of 337 pregnant women were recruited into the study, with 222 abnormal placentations (85 were classified as LP, 72 as PP and 65 as PAS) and 155 controls. Among the participants, 37 women (9.81%) were diagnosed with HDPs. The incidence of HDPs was significantly lower in the PP (4.2%) and PAS (7.7%) groups compared to the control group (12.3%) (p [Med-Science 2024; 13(4.000): 1007-13]